Efficacy of Acceptance and Commitment Therapy in the Treatment of Social Phobia among Adolescents in Secondary Schools in Oyo State, Nigeria - Segun Oyetunde Babalola; Ajibola Olusoga Ogunyemi (Annual Journal of Technical University of Varna, 2019)
Social phobia is a mental health problem that has been repeatedly linked with adolescents. This study therefore investigated the efficacy of Acceptance and Commitment therapy (ACT) on social phobia among secondary school adolescents in Oyo State, Nigeria. The study adopted a pretest – posttest control group quasi experimental design. The sample comprised of 104 secondary school adolescents identified with some levels of social phobia from the two randomly selected schools among the three senatorial districts of Oyo State. The selected students, grouped by schools and subsequently, treatment groups, were 51 and 53 for the control and experimental groups, respectively. The experimentation spanned a period of eight weeks, with ACT administered to the experimental group and placebo of leadership styles administered to the control group. The Social Phobia Inventory (SPI) was adopted and used for screening and in pretest and posttest stages. A statistical hypothesis was formulated and tested at 0.05 level of significance by means of the Analysis of covariance (ANCOVA). It was found that treatment with ACT significantly reduced the level of social phobia among school-going adolescents. ACT was therefore recommended for use in relieving school-going adolescents suffering from social phobia.